Evaluation of muscle tears in professional athletes using diffusion-weighted imaging and apparent diffusion coefficient: preliminary results - Nocerino, Elisabetta Antonia; Aliprandi, Alberto; Tavana, Rodolfo; Mazzoni, Stefano; Di Leo, Gianni; Genovese, Eugenio Annibale (Acta Biomedica Atenei Parmensis, 2019)
Purpose: Many studies have evaluated the role of DWI in musculoskeletal diseases but less is known on muscle tears. Especially for professional athletes, muscle injuries are responsible for large time lost. The aim of this study was to investigate on potential relationship between the muscle tear degree and the diffusion characteristics. Methods: In this retrospective study, patients signed a comprehensive consent form according to Good Clinical Practice guidelines before proceeding with all examinations. It satisfied all the requirements of the Declaration of Helsinki and the Italian national law for the protection of personal data. We have analyzed 38 professional athletes (36 males; mean age±standard deviation 27±8 years) with a muscle tear. They were 26 football and 12 athletics players, with clinically suspected injuries of the lower limbs muscles. All of patients underwent a 1.5-T MRI with standard protocol (STIR, TSE T2, SE T1, PD T2, PD fat sat T2) plus the DWI sequences with 0, 400 and 800 B-values (s/mm2). Per each B value, an experienced radiologist measured the signal intensity (SI, in arbitrary units [au]) using a region of interest (ROI) placed within the tear on DWI images. SI drop off at the third B value was calculated referred to the first B value. Similarly, ADC was measured using the ADC map in a small ROI within the tear. Bivariate associations were evaluated using the Student t test. Logistic regression was performed using the tear degree as dependent variable. Data were given as mean±standard deviation. Results: According the Muller-Wohlfarth classification, the 38 muscle tears were classified in type 3a in 22/38 cases and 3b in 16/38 cases. At bivariate analysis, 3a-tears had a SI at the third B value (24±9 au) lower (P=0.003) than that of 3b-tears (34±9 au). Similarly, 3a-tears had a SI drop off (73±10%) lower (P=0.008) than that of 3b-tears (82±9%). ADC was not significantly associated to tear degree (P=0.093). At regression analysis, SI at the third B value was the only independent predictor of the tear degree (P=0.032), while the SI drop off was borderline significant (P=0.070). Conclusion: This preliminary data showed a positive correlation between the degree of muscle tears and the SI at the third B-value. Compared to 3a- tears, 3b-tears tend to show higher SI and a higher SI drop off.